SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI ATM DAN AGEN LINK DI KOTA TEMBILAHAN - Saputra, Feri Adha; Abdullah; Jibril, Muhammad (Program Studi Teknik Industri, 2023)
In Indragiri Hilir Regency, there are many ATM locations at several points in the downtown area of Tembilahan and Link Agents spread throughout Indragiri Hilir Regency. However, not all people in Indragiri Hilir Regency know the location of ATMs and Link Agents, especially those that are far from the center of Tembilahan city and from other areas that have just set foot in the downstream Indragiri district. So the researchers tried to build a Web-based Geographic Information System, by mapping the locations of ATMs and Link Agents spread across Indragiri Hilir District. The purpose of this study is to design a web-based Geographic Information System application that can provide accurate data needed by users who need information. This study uses the Waterfall development model or